Structural change in the economy of Nigeria - Adeyinka, Adedeji; Salau, Sheu; Vollrath, Dietrich (International Food Policy Research Institute, 2013)
We document that structural change accounts for approximately one-fifth of the total change in labor productivity in Nigeria between 1996 and 2009. Labor moved out of the agricultural and wholesale and retail trade sectors into manufacturing, transportation and communications, business services, and general services. While structural change did occur in this period, significant gains to aggregate labor productivity are still available from further shifts of labor to higher-productivity sectors. We discuss the factors limiting structural change, which include poor agricultural productivity, insufficient infrastruc-ture to support high productivity sectors, and a lack of appropriate skills in the labor force. We calculate that the gains still available to Nigeria from structural change are equivalent to an increase in value-added of 25 percent, given the existing productivity levels of sectors in 2009.